Inovasi Strategi Mengajar Guru dalam Pembelajaran Fikih untuk Meningkatkan Mutu Belajar Siswa Kelas I di MIN 3 Way Kanan - Liliyani Liliyani (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to determine the strategies used by teachers in improving the quality of Fiqh learning for class I at MIN 3 Way Kanan. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The main instrument in this study is an interview guideline to identify problems that occur in the learning process. Based on the results of the study, it was found that teachers have not been consistent in implementing learning strategies, methods, and supporting media so that students have difficulty in understanding the material well. This is due to the lack of creativity and innovation of teachers in compiling and developing Learning Implementation Plans (RPP). In improving the quality of Fiqh learning, the strategies used by teachers include the implementation of student-centered learning with an inquiry approach, which can make the learning process more active and enjoyable. Teachers also need to compile RPPs creatively and innovatively, understand learning objectives, and find additional learning resources besides LKS.